1990
DOI: 10.1007/bf00189723
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function relationships in identified afferent neurones

Abstract: The review deals with structure-function relationships in primary afferent and spinal cord neurones that were intracellularly injected with a marker substance (mostly HRP) after physiological identification. At the level of dorsal root ganglion (DRG) cells, there is a significant correlation between soma size and conduction velocity (or diameter) of the afferent fibre for most subpopulations of DRG cells, but the scatter of data is considerable, so that the size of a DRG cell soma cannot be predicted from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 97 publications
2
18
0
1
Order By: Relevance
“…DRG cell types in the present study were all considered to have small (types 7 and 17) or medium (types 5, 6, 8, 14, 15, 16, and 18) cell diameters. Since DRG cell diameter correlates with conduction velocity-based classification schemes of the peripheral fiber size (Gasser and Grundfest 1939;Lawson and Waddell 1991;Mense 1990), our results agree with the notion that both the distal colon and the glans penis/distal urethra have a high number of small myelinated A-fibers and unmyelinated C-fibers (Delcambre et al 2011;Johnson and Halata 1991;Johnson and Murray 1992). Although there were a small number of large-diameter cells that remained intact after the enzymatic digestion from each of the tracer-injected animal groups, these are typically difficult to patch in the acute culture preparation.…”
Section: Identification Of Cell Types Innervating the Colon And Penissupporting
confidence: 87%
“…DRG cell types in the present study were all considered to have small (types 7 and 17) or medium (types 5, 6, 8, 14, 15, 16, and 18) cell diameters. Since DRG cell diameter correlates with conduction velocity-based classification schemes of the peripheral fiber size (Gasser and Grundfest 1939;Lawson and Waddell 1991;Mense 1990), our results agree with the notion that both the distal colon and the glans penis/distal urethra have a high number of small myelinated A-fibers and unmyelinated C-fibers (Delcambre et al 2011;Johnson and Halata 1991;Johnson and Murray 1992). Although there were a small number of large-diameter cells that remained intact after the enzymatic digestion from each of the tracer-injected animal groups, these are typically difficult to patch in the acute culture preparation.…”
Section: Identification Of Cell Types Innervating the Colon And Penissupporting
confidence: 87%
“…The possible functional significance of anatomical changes secondary to the degenerative alterations of primary afferents will also be dealt with in some detail. (Andres, 1961;Lawson, Caddy & Biscoe, 1974 Mense, 1990). In this article, sensory ganglion cells giving rise to myelinated and unmyelinated axons will be referred to as A-fibre and C-fibre primary sensory neurones, respectively.…”
mentioning
confidence: 99%
“…Combining intracellular recording with intracellular injection of a marker, such morphological variety of the sensory ganglion neurons has recently been directly related to peripheral nerve conduction velocity in individual neurons (Yoshida and Matsuda, 1979; Harper and Lawson, 1985; Cameron et al, 1986; Lee et al, 1986;Hoheisel and Mense, 1987;Mense, 1990;Nagy et al, 1993). Hoheisel and Mense (1987) revealed a particularly detailed relationship between morphological characteristics and conduction velocity for the neurons in the dorsal root ganglion, in which it was reported that the neurons conducting in the A-p range had thick axons, whereas axons of neurons in the A-6 range were different according to their conduction velocities: i.e., neurons conducting in the fastest range had myelinated axons on both sides of the bifurcation; those conducting in the intermediate range had a myelinated peripheral axon and an unmyelinated central Accepted March 24, 1995.…”
Section: Indexing Terms: Functional Morphology Intracellular Horseramentioning
confidence: 99%